Management of Pesantren in Improving Nationalism and Addressing Social Problems in Disruption Era - Siti Aimah; Muhammad Nasih; Nihayatul Wafiroh; Fathiyah Mohd Fakhruddin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The purpose of this study is to find a model of pesantren that survives in moderation of education and nationalism and analyze the role of pesantren in overcoming the humanitarian crisis in the era of disruption. This type of research is a case study with a qualitative approach. The results showed that as the largest pesantren in Banyuwangi Regency, Pesantren Darussalam Blokagung exemplifies its success in integrating religious and general education values in educational moderation, building a spirit of nationalism by actualizing a sense of love for the country, rejecting radical ideologies and opposing terrorism, and helping to realize pluralism in the context of security. Pesantren Darussalam Blokagung also plays an important role in multicultural education that teaches religious tolerance and moderation, mutual respect and appreciation in simplicity and independence. In addition, it also helps to overcome humanitarian crises by establishing the Darussalam Social Institute (LBD) which provides scholarships to underprivileged students, the Darussalam Counseling Center (DCC), a therapy center for mental problems and the provision of special dormitories in pesantren for students affected by humanitarian crises and social problems.